Ethical implications in the evaluation of complex contexts related to COVID-19 - Anthony Copez-Lonzoy; Ana L Vilela-Estrada; G.J. Meléndez-Torres (Interacciones)
Background: The pandemic caused by Sars-cov-2 has generated multiple sustained efforts for its identification, characteristics and mobility of the disease that to date has repercussions worldwide. Given this need, it is necessary to have updated information considering transparent research processes. Method: a critical review of the current literature on COVID-19 research. Conclusions: It is essential to have ethical procedures in the different phases of research that can go beyond personal interests and that guarantee the preservation of people's welfare in the reduction of possible damage to health globally, adequate procedures in the collection of information that is not built to the measure of the researchers, to avoid involuntary segregation of the participants and that this leads to a reduction of significant damage due to implicit biases that are generated by poor planning that pursues the scoop instead of social good.